MAKNA DAN KARAKTERISTIK AYAT AL-MAKKY DAN ALMADANY SERTA URGENSI MEMPELAJARINYA - Hasna ‘Afifah; Halimatul Sakdiah (CV. Adiba Aisha Amira, 2022)
The Qur'an was revealed to the Prophet Muhammad (PBUH) gradually over a period of approximately 23 years. Some of the verses of the Qur'an were revealed in the city of Mecca and some were revealed in the city of Medina, some were revealed in the summer, and some were revealed in the winter, some were sent down while traveling, and some were revealed at night. as well as during the day. This condition aroused the attention of scholars and commentators to conduct further research on the Qur'an, especially with regard to the place where the verse was revealed, thus giving rise to a new knowledge of the Qur'an in order to gain a complete understanding of understanding and interpreting the verses of the Qur'an, namely Makki and Madani Science. According to the commentators, Makkiyah and Madaniyah include issues of space, time, subject and content. And the benefits of studying this knowledge include being able to distinguish between Nasikh and Mansukh verses, knowing the characteristics of Makki and Madani language styles in the Qur'an, and this knowledge is very useful for the Mufassir, namely as a tool in the interpretation of the verses. Al-Qur'an.